Angklung Sered Balandongan: Pelestarian dan Pembudayaannya di Kabupaten Tasikmalaya Tahun 1995-2017 - Amelia, Tia (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This research describes the preservation and enculturation of Angklung Sered Balandongan in Tasikmlaya District in 1995-2017. This research comes from the confusion and anxiety of the arts Angklung researchers Sered balandongan which until now has not been widely recognized by the public. Even had extinguished before finally start there research by artists who later developed in the area of education. Broadly speaking, this study answers the question